2010
DOI: 10.1016/j.jneuroim.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against the voltage-dependent anion channel (VDAC) and its protective ligand hexokinase-I in children with autism

Abstract: Autistic children show elevated serum levels of autoantibodies to several proteins essential for the function of normal brains. The voltage-dependent anion channel, VDAC, and hexokinase-I, a VDAC protective ligand, were identified as targets of this autoimmunity in autistic children. These autoantibodies were purified using immunoaffinity chromatographic techniques. Both antibodies induce apoptosis of cultured human neuroblastoma cells. Because VDAC and hexokinase-I are essential for brain protection from isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Therefore, newly identified autoantibodies, such as anti-KLHL12 and anti-HK1, could be important biomarkers for differentiating PBC from other autoimmune diseases. Despite the reported presence of anti-KLHL12 antibody in Sj€ ogren's syndrome (28) and anti-HK1 antibody in the sera of children with autism (29), the specificity of both anti-KLHL12 and anti-HK1 antibodies in PBC was very high (≥95%). A small percentage of clinically proven PBC are AMA negative (30).…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, newly identified autoantibodies, such as anti-KLHL12 and anti-HK1, could be important biomarkers for differentiating PBC from other autoimmune diseases. Despite the reported presence of anti-KLHL12 antibody in Sj€ ogren's syndrome (28) and anti-HK1 antibody in the sera of children with autism (29), the specificity of both anti-KLHL12 and anti-HK1 antibodies in PBC was very high (≥95%). A small percentage of clinically proven PBC are AMA negative (30).…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, the signal intensities of these two isoforms were highly correlated. Additionally, the HK1 has been identified as an autoantigen associated with autistic children, and anti-HK1 autoantibodies were shown to impair growth and induce apoptosis in cultured human neuroblastoma cells (97). It would be interesting to determine whether HK1-positive patients also suffer from similar nervous system-associated impairments.…”
Section: New Pbc Biomarkers By Human Proteome Microarraysmentioning
confidence: 99%
“…Because t-PA activity is enhanced by VDAC (7) and because both t-PA and Pg activation are affected by the interaction of these ligands with either VDAC or GRP78, we hypothesized a functional cell surface interaction between these four components in the brain. For these studies, we used the human neuroblastoma cell line SK-N-SH as an in vitro model because these cells express VDAC on the cell surface (19). We investigated the expression of GRP78 in these cells and found that GRP78 co-localizes with VDAC on the cell surface.…”
mentioning
confidence: 99%